Inside Cover: Construction of Optically Active Quaternary Propargyl Amines by Highly Enantioselective Zinc/BINOL‐Catalyzed Alkynylation of Ketoimines (Chem. Eur. J. 36/2013). Issue 36 (27th August 2013) - Huang, Gaochao; Yin, Zengsheng; Zhang, Xingang
<x xml:space="preserve">Abstract</x> Chinese mythology was used to describe the challenges involved in the catalytic enantioselective alkynylation of ketoimines. The arrow shows the alkynylzinc reagent generated from alkyne and Me2Zn; BINOL, an accelerator for the reaction, is the bow. The substrates ketoimines are the suns. The three suns shot down in the sea are the three types of products, chiral quaternary propargyl amines. For more details, see the Full Paper by X. Zhang et al. on page 11992 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>